2016
DOI: 10.18203/2320-1770.ijrcog20164673
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of gestational trophoblastic disease in a rural tertiary centre of Haryana, India

Abstract: Background: The reported incidence of GTD varies widely worldwide, from a low of 23 per 100,000 pregnancies (Paraguay) to a high of 1,299 per 100,000 pregnancies (Indonesia). The reported incidence of GTD in India is inconsistent therefore we planned to do an analysis of the GTD at our institute which is a referral tertiary center of Haryana.Methods: Records of patients of GTD admitted from January 2014 to June 2016 were analyzed and incidence per 1000 deliveries was calculated. The demographic profile, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…In present study most of the women (66%) with molar pregnancies are presented in their second trimester with a mean gestational age of 12.8±2 weeks. It is comparable to the study by Lakra et al (6), who reported 13.8±3 weeks as the mean age of gestation. Increase in diagnostic services over the years, have led to early recognition of the disease.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In present study most of the women (66%) with molar pregnancies are presented in their second trimester with a mean gestational age of 12.8±2 weeks. It is comparable to the study by Lakra et al (6), who reported 13.8±3 weeks as the mean age of gestation. Increase in diagnostic services over the years, have led to early recognition of the disease.…”
Section: Resultssupporting
confidence: 90%
“…81% had pallor but 13.8% required blood transfusion. Lakra et al reported that 76.3% patients had pallor and 57.9% received blood transfusion (6).There were no ICU admissions or mortality in our study.…”
Section: Resultssupporting
confidence: 38%
See 3 more Smart Citations